Sunset of the sabertooth - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1996)
The magic tree house transports Jack and Annie on a mission to the Ice Age where they encounter Cro-Magnons, cave bears, sabertooth tigers, and woolly mammoths.
Book Links (A.L.A.).
Book Links (A.L.A.), July 2005.
3.3
3-6
Keywords: Animals, Fossil -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Magic -- Juvenile fiction; Prehistoric peoples -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Prehistoric animals -- Fiction; Prehistoric peoples -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Prehistoric animals -- Fiction; Prehistoric peoples -- Fiction; Time travel -- Fiction; Tree houses -- Fiction